Peran Wali Pemasyarakatan dalam Pembinaan Warga Binaan Pemasyarakatan di Lembaga Pemasyarakatan Kelas IIA Wirogunan Yogyakarta - Ajeng Kusumawardani (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2022)
Prisoners are part of the community who get sanctions for their criminal acts. The role of the correctional guardian is needed in the process of fostering the Correctional Inmates who are the target of the guidance carried out in the Correctional Institution. This research is a qualitative research with a descriptive approach which aims to describe the role of correctional guardians in fostering correctional inmates in the Class IIA prison in Yogyakarta. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique begins with data collection, data reduction, data triangulation, data presentation and conclusion drawing and verification. The results of this study indicate that the coaching process at the Class IIA Yogyakarta Lapas runs effectively according to the goals of the correctional process through the role of the correctional guardian as a facilitator, communicator, and motivator. Efforts that need to be maximized in coaching require a psychologist or special social worker as a correctional guardian.